2018
DOI: 10.1111/eci.12886
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 in end‐stage heart failure, before and after support with a left ventricular assist device

Abstract: BackgroundThe interleukin‐33 (IL‐33)/suppressor of tumorigenicity 2 (ST2) pathway is suggested to play an important role in fibrosis, remodelling and the progression of heart failure (HF). Increased soluble (sST2) levels are associated with adverse outcome in the average HF population. Less is known about sST2 levels in end‐stage HF. Therefore, we studied sST2 levels in end‐stage HF and the effect of unloading by left ventricular assist device (LVAD) support on sST2 levels.Method and resultsSerial plasma measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 14 publications
1
32
1
Order By: Relevance
“…Tseng et al found that the patients in the endstage of HF had a higher sST2 level compared with the patients in the NYHA stage II and III of HF, but the level could decrease within 3 months after implantation of left ventricular assist device [16]. Shah et al [17] found that sST2 levels were significantly associated with abnormal changes in function and structure such as ventricular enlargement, LV diastolic dysfunction etc. In our study, Spearman correlation analysis results indicated that sST2 could be an independent risk factor for heart failure diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tseng et al found that the patients in the endstage of HF had a higher sST2 level compared with the patients in the NYHA stage II and III of HF, but the level could decrease within 3 months after implantation of left ventricular assist device [16]. Shah et al [17] found that sST2 levels were significantly associated with abnormal changes in function and structure such as ventricular enlargement, LV diastolic dysfunction etc. In our study, Spearman correlation analysis results indicated that sST2 could be an independent risk factor for heart failure diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The sST2 levels were positively correlated with the degree of cardiac fibrosis ( 150 ). Along these lines, it has been recently observed that left ventricular assist device (LVAD) resulted in a significant drop in sST2 levels with normalization within 3 months post-implantation, thus lessened heart fibrosis and inflammation ( 151 ).…”
Section: Il-33/st2 Axis In Heart Fibrosismentioning
confidence: 99%
“…Thus a relationship exists between sST2 and cardiac dysfunction [41,66]. A recent study showed that sST2 plasma levels normalized within 3 months post-implantation of a left ventricular assist device (LVAD) in endstage HF patients [67]; this indicates that unloading the heart by LVAD placement lessens fibrosis. Because these are end-stage HF patients, many of whom will have multi-organ involvement, this finding may not be limited to the heart.…”
Section: Fibrosis Marker Sst2mentioning
confidence: 99%